Following the Government Playbook? Channeling Development Assistance for Health through Country Systems - Piatti-Funfkirchen, Moritz; Hashim, Ali; Alkenbrack, Sarah; Gurazada, Srinivas (World Bank, Washington, DC, 2021)
Development partners (DPs) contribute to a significant share of total health financing, especially in low-income countries, and support the achievement of universal health coverage (UHC). However, if DP support is not well aligned with government systems, it can lead to inefficiencies, such as poor prioritization, fragmentation, and duplication of activities, and inhibit the government’s ability to maintain effective stewardship over sector activities. This note develops a comprehensive interpretation of the term ‘country systems’ in a public financial management (PFM) environment along with a checklist across the budget cycle that can be used to assess whether DPs in a given country are aligned to various PFM aspects. Undertaking an assessment is expected to have the following benefits: to provide a better understanding of the DP financial architecture and contribute to the literature of DP alignment and aid effectiveness; to articulate a clear baseline of DP financing modalities to allow for establishing a logical framework that will help articulate a reform program and strengthen mutual accountability. to foster learning across countries and DPs.